Testing value investing strategies and analyzing their characteristics: Evidence from North and Latin America - Pakkala, Pasi (My University, 2014)
This thesis aims to study performance of value stocks and compare results from Latin and North America. These are compared to understand how these markets differ, and how value stock returns and behaviour differ between these emerging and developed economies. This research provides value due to the low amount of value investing research performed with Latin American data. Even previously performed research might not be valid anymore due to quick evolvement of the market during the 21st century. Latin America provides an interesting setting for a study due to its unique characteristics that include location, similar cultures and strong economic growth. Main part of the thesis is to perform research with price-to-book, size, sales-to-price, dividend ratio, price-to-cashflow, and with price-to-earnings ratio to test their effectiveness in these markets during given timeframe from the year 2000 till the end of 2013. Best performing ratios are then studied further to understand their performance and possibly to see how they could be improved. Given results are used to understand best investment ratios, how Latin and North American markets differ and if one or the other should be preferred. Detailed look is also given to behavioural finance theories and specifics of economic development of American markets to understand their development and future possibilities and challenges. Results show strong performance from size and price-to-sales strategies in American continents. Deeper study into these strategies reveals market capitalization is an important part of the success of companies as small companies are a vital part of sales- to-price strategy’s success as well. Correspondingly long-term holding periods of over five years are generally better performing. It also becomes clear that using one ratio to group stocks is efficient enough with large groups that are then likely to contain a small number of outperforming stocks that bring majority of returns. To form small portfolios investor is likely better off if he avoids strict ratio based picking strategies, but use one effective ratio to group the stocks and then eliminate stocks with the worst factors, by using criteria such as market outlook and quality of management.
Keywords: Value investing; behavioral finance; economic development; Latin America; North America; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|